PENGADOPSIAN KEBIJAKAN DEKRIMINALISASI ILLICIT DRUGS FOR PERSONAL USE DI PORTUGAL OLEH UNODC - Ramadhani, Valentina Dea; Utomo, Tri Cahyo; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
Drugs abuse is a criminal act which cause harm to state’s health,social and economy circumstances. So far, United Nation on Drugsand Crime (UNODC) drugs policy tend to do law enforcement andoperations to stifle drug supply. Portugal raise a different policy in2001 where drug use is no longer a crime act and only consider asadministrative offences. It show positive result and they try to promoteit into the Commission in Narcotic Drugs (CND). Using liberalinstitutionalism and global public policy theory, this research tries toanalyze the process of global policy adoption to challenge drugsabuse. It seeks to describe what kind of global policy adoption happenin CND is and the process in adopting national policy into globalpolicy. As the result, UNODC did not fully adopting Portugal’s drugsdecriminalization policy. But, Portugal and European Union’s role inpolitical process in CND earn policy adoption to the importance ofaccess to rehabilitation and treatment for drug users as a strategy tochallenge drug abuse.